Spatial Variability of Oil Palm Leaf Nutrients and Yield - Mohd Junusi, Riduan (2006)
In recent times, among the major problems in oil palm plantation is the lack of proper interpretation of yield maps for site-specific management, the identification, and understanding of the causal factors influencing the variability of oil palm yields. The ability to find and comprehend the leaf factors influencing yield variability of oil palm will help in managing the plantation efficiently for better yield. The study of Spatial Varibility of Oil Palm Leaf Nutrients and Yield was carried out at Dusun Durian Estate, Golden Hope Plantations Berhad, Banting, Selangor, in a 15 ha plot which was a coastal oil palm plantation. The objective of this study was to obtain accurate and timely information about the spatial distribution and status of nutrients in the leaf tissue using Geographic Information System (GIs) for precision farming of oil palm plantation. Collection of leaf tissue data were conducted using systematic sampling and an AgGPS Trimble was used to precisely determine the sampling locations. Geostatistics (GS+) software and classical statistics were used for data analysis. Leaf nutrient analysis illustrated that the leaf nutrient variability of N, P, K, Ca and Mg from year 2000 to 2003 could be classified as low whereas coefficient of variation (CV) values of 2.0 to 2.2, 1.9 to 3.0 and 1.9 to 5.3, 5.7 to 7.4 and 6.6 to 7.4 respectively. Based on the semivariance analysis, leaves nutrients have a moderately spatial dependence with the lag distances of 31 1 to 314 m, 161 to 249 m, 185 to 311 m and 169 to 314 m for N, P, K and Ca, respectively. Meanwhile, Mg have a strong spatial dependence (S) with the lag distance is 94 to 183 m. The variability of fresh fruit bunch (ffb) is moderate and is moderately spatial dependence with the lag distance of 310 to 314 m. There is a strong relationship between FFB yield, N and P in leaf tissue. This result implies that N and P in leaf tissue can be used to determine the FFB yields.